Identification and validation of coding and non-coding RNAs involved in high-temperature-mediated seed dormancy in common wheat - Jiang, Hao; Gao, Wei; Jiang, Bing-li; Liu, Xue; Jiang, Ya-ting; Zhang, Li-tian; Zhang, Yue; Yan, Sheng-nan; Cao, Jia-Jia; Lu, Jie; Ma, Chuan-xi; Chang, Cheng; et al. (Frontiers in Plant Science, 2023)
Seed dormancy (SD) significantly decreases under high temperature (HT) environment during seed maturation, resulting in pre-harvest sprouting (PHS) damage under prolonged rainfall and wet weather during wheat harvest. However, the molecular mechanism underlying HT-mediated SD remains elusive. Here, the wheat landrace ‘Waitoubai’ with strong SD and PHS resistance was treated with HT from 21 to 35 days post anthesis (DPA). Then, the seeds under HT and normal temperature (NT) environments were collected at 21 DPA, 28 DPA, and 35 DPA and subjected to whole-transcriptome sequencing. The phenotypic data showed that the seed germination percentage significantly increased, whereas SD decreased after HT treatment compared with NT, consistent with the results of previous studies. In total, 5128 mRNAs, 136 microRNAs (miRNAs), 273 long non-coding RNAs (lncRNAs), and 21 circularRNAs were found to be responsive to HT, and some of them were further verified through qRT-PCR. In particular, the known gibberellin (GA) biosynthesis gene TaGA20ox1 (TraesCS3D02G393900) was proved to be involved in HT-mediated dormancy by using the EMS-mutagenized wheat cultivar Jimai 22. Similarly, a novel gene TaCDPK21 (TraesCS7A02G267000) involved in the calcium signaling pathway was validated to be associated with SD by using the EMS mutant. Moreover, TaCDPK21 overexpression in Arabidopsis and functional complementarity tests supported the negative role of TaCDPK21 in SD. We also constructed a co-expression regulatory network based on differentially expressed mRNAs, miRNAs, and lncRNAs and found that a novel miR27319 was located at a key node of this regulatory network. Subsequently, using Arabidopsis and rice lines overexpressing miR27319 or lacking miR27319 expression, we validated the positive role of miR27319 in SD and further preliminarily dissected the molecular mechanism of miR27319 underlying SD regulation through phytohormone abscisic acid and GA biosynthesis, catabolism, and signaling pathways. These findings not only broaden our understanding of the complex regulatory network of HT-mediated dormancy but also provide new gene resources for improving wheat PHS resistance to minimize PHS damage by using the molecular pyramiding approach.